ANALYSIS OF DEPOK CITY REGIONAL FINANCIAL PERFORMANCE IN 2018-2021 - Mudrikah Anurohman; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This study aims to determine the financial performance of Depok City Government in 2018- 2021 seen from: fiscal decentralization degree ratio, fiscal capacity, local financial independent ratio, regional financial efficiency ratio, PAD effectiveness ratio, and harmonious ratio. This research is quantitative descriptive. The results of the analysis show that the Depok City Government's financial performance when viewed from fiscal decentralization degree ratio categorized by sufficient because the average ratio is 39,53%. Average fiscal capacity is 2,65 point and categorized by very high. Regional financial independence ratio categorized by medium in 67,91% . The regional financial efficiency ratio is still considered lack of efficient because it is 98.02% point. PAD effectiveness ratios can be said to be very effective because the average effectiveness has exceeded 100%. Harmonious ratio that the majority of funds owned by the Depok City Government are still prioritized for operational expenditure needs. This causes the ratio of capital expenditure to be relatively small.